Tuberculosis in international immigrants: Profile and vulnerability of cases residing in the municipality of São Paulo, Brazil - Denise Gonçalves; Rubia Laine de Paula Andrade; Antônio Ruffino Netto (Elsevier, 2022)
Objective: To analyze the profile of immigrants with tuberculosis (TB) and to identify the associated vulnerability characteristics. Methods: A cross-sectional study which used TB-WEB data from cases residing in São Paulo in 2016 (203 immigrants and 6,069 non-immigrants). The variables were analyzed using prevalence ratio and confidence intervals. Results: Among the immigrant cases, 67% were Bolivians. When compared to non-immigrants, immigrants were younger and frequently indigenous or presenting yellow ethnicity. They were also associated with a higher education level. We observed less immigrants having extrapulmonary TB and comorbidities, such as HIV/AIDS, diabetes mellitus, or drug use. Compared to cured cases, immigrants were not associated with treatment default and death, but they were associated with transfer to another state/country. Conclusions: Younger individuals and higher education levels were identified among immigrants, as well as a lower occurrence of comorbidities and drug use. It is believed that these results have led immigrants to more favorable outcomes of TB treatment.